2015
DOI: 10.1021/acsnano.5b01203
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an Aptamer–SiRNA Chimera-Modified Tissue-Engineered Blood Vessel for Cell-Type-Specific Capture and Delivery

Abstract: The application of tissue-engineered blood vessels (TEBVs) is the main developmental direction of vascular replacement therapy. Due to few and/or dysfunctional endothelial progenitor cells (EPCs), it is difficult to successfully construct EPC capture TEBVs in diabetes. RNA has a potential application in cell protection and diabetes treatment, but poor specificity and low efficiency of RNA transfection in vivo limit the application of RNA. On the basis of an acellular vascular matrix, we propose an aptamer-siRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Chen et al. also constructed an aptamer‐siRNA chimera‐modified tissue‐engineered blood vessel (TEBV) containing two components of CD133 aptamer‐ADK siRNA chimera and TEBV scaffold for CD133 + cell capture as well as aptamer‐siRNA chimera delivery . PEI/PEG‐AuNPs were used to connect the CD133‐ADK siRNA chimera and TEBV scaffold.…”
Section: Chemically Modified Nucleic Acid Drugs For Target Specific Imentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al. also constructed an aptamer‐siRNA chimera‐modified tissue‐engineered blood vessel (TEBV) containing two components of CD133 aptamer‐ADK siRNA chimera and TEBV scaffold for CD133 + cell capture as well as aptamer‐siRNA chimera delivery . PEI/PEG‐AuNPs were used to connect the CD133‐ADK siRNA chimera and TEBV scaffold.…”
Section: Chemically Modified Nucleic Acid Drugs For Target Specific Imentioning
confidence: 99%
“…126 Chen et al also constructed an aptamer-siRNA chimera-modified tissue-engineered blood vessel (TEBV) containing two components of CD133 aptamer-ADK siRNA chimera and TEBV scaffold for CD133 + cell capture as well as aptamer-siRNA chimera delivery. 127 PEI/PEG-AuNPs were used to connect the CD133-ADK siRNA chimera and TEBV scaffold. CD133 aptamer specifically captured CD133 + cells in bloodstream and self-delivered aptamer-siRNA chimera to the captured CD133 + cells.…”
Section: Aptamer-oligonucleotide Conjugatesmentioning
confidence: 99%
“…(2) RNA could be specifically and stably delivered to target cells, which can avoid the disadvantages of RNA‐modified TEBVs, including easy degradation and poor targeting. (3) PEI/AuNP was selected as the bridge between TEBV scaffold and exosomes, which can protect exosomes from the high shear blood flow and enhance the stability of TEBV . (4) The exosomes of MSCs with the function of immune privilege and induction of immune tolerance were selected, which might be derived from patient's own cells or allogeneic cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inhibition of ADK could protect cell against the damage of pathogenic factors. In the meantime, ADK inhibited cells can sustainably release adenosine which is an optimizing molecule for local microenvironment . EPC capture and antiapoptosis are functions of klotho …”
Section: Introductionmentioning
confidence: 99%
“…Very recently, using an antiprostate specific membrane antigen aptamer-siRNA chimera, Diao et al (2016) specifically controlled the growth of a prostate tumor. In another interesting study, Chen et al (2015) modified tissue-engineered blood vessels with an aptamer-siRNA chimera and achieved cell-specific delivery and capture. Furthermore, that study showed that PEGylation and 2'fluoro modification of the aptamer increased its stability and specificity.…”
Section: Aptamer-based Chimerasmentioning
confidence: 99%